PKC delta (PKCδ) promotes tumoral progression of human ductal pancreatic cancer - Mauro, Laura Valeria (2010)
OBJECTIVE: Our objective was to study the role of protein kinase C delta (PKCdelta) in the progression of human pancreatic carcinoma. METHODS: Protein kinase C delta expression in human ductal carcinoma (n = 22) was studied by immunohistochemistry. We analyzed the effect of PKCdelta overexpression on in vivo and in vitro properties of human ductal carcinoma cell line PANC1. RESULTS: Human ductal carcinomas showed PKCdelta overexpression compared with normal counterparts. In addition, in vitro PKCdelta-PANC1 cells showed increased anchorage-independent growth and higher resistance to serum starvation and to treatment with cytotoxic drugs. Using pharmacological inhibitors, we determined that phosphatidylinositol-3-kinase and extracellular receptor kinase pathways were involved in the proliferation of PKCdelta-PANC1. Interestingly, PKCdelta-PANC1 cells showed a less in vitro invasive ability and an impairment in their ability to migrate and to secrete the proteolytic enzyme matrix metalloproteinase-2. In vivo experiments indicated that PKCdelta-PANC1 cells were more tumorigenic, as they developed tumors with a significantly lower latency and a higher growth rate with respect to the tumors generated with control cells. Besides, only PKCdelta-PANC1 cells developed lung metastasis. CONCLUSION: Our results showed that the overexpression of PKCdelta in PANC1 cells induced a more malignant phenotype in vivo, probably through the modulation of cell proliferation and survival, involving phosphatidylinositol-3-kinase and extracellular receptor kinase signaling pathways.